Network evolution, success, and regional development in the European aerospace industry - Daniel Guffarth; Michael J. Barber (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2014)
The success breeds success hypothesis has been mainly applied to theoretical network approaches. We investigate the European aerospace industry using data on the European Framework Programmes and on Airbus suppliers, focusing on the success breeds success hypothesis at four levels of analysis: the spatial structure of the European aerospace R&D collaboration network, its topological architecture, the individual actors that make up the network, and through a comparison of the Airbus invention and production networks. On the spatial level, SBS is favored: successful regions maintain their position and grow on a large scale, especially so for regions that have strongly participated from the very beginning. The regional hub structure is mirrored in the architecture of the European aerospace R&D collaboration network, where well-connected hub organizations play a key role in shaping the structure of the network through their many collaborative partnerships and do so in a way that strategically positions themselves with greater ability to access and regulate knowledge flows, as assessed by several centrality measures. Only successful organizations have the ability to form so many ties, with success thus breeding success in the European aerospace R&D collaboration network. The importance of the core organizations made clear through the centrality analysis is further supported by the analysis of weak ties, where we observe that the core organizations are connected to the rest of the network with many weak ties, thereby confirming their outstanding positions in the European aerospace R&D collaboration network as being able to access knowledge or other resources. With the combination of the R&D collaboration network and the Airbus production network on a spatial level, we see additional support for SBS, as those regions whose actors are frequent participants in both networks show the greatest share of successful actors. The European aerospace industry shows an ambidextrous character as a whole, which is nonetheless insufficient to avoid recent and future challenges demanding a strong emphasis on production skills.
urn:nbn:de:bsz:100-opus-10363
Keywords: D85; L14; L93; O38; R11; R12; Z18; 330; R&D collaboration network; success breeds success; aerospace industry; European Framework Programmes